Tok Kenali: penggemblengan modal insan satu tinjauan terhadap generasi pra-kemerdekaan = Tok kenali: the mobilazation of 'human capital', a study of the generation pre- independence day - Yaacob, Adli; Yaacob, Solehah@Nik Najah Fadilah; Abd. Rahman, Akmal Khuzairy; Yaacob, Hakimah; Yaacob, Bahruddin (Global Academic Excellence (M) Sdn Bhd (GAE), 2021)
Tok Kenali is an ulama who can be regarded as one of the great leaders in the Malay Archipelago in the 20th century who diligently sought the meaning of truth and fought for the right to freedom, especially in the state of Kelantan. He is recognized as the greatest scholar of the three figures which is very ideal by the diversity of his activities and contributions to the civilization of the Malay Archipelago. His spirit that wanted to see a change in the dimensions of the Malay community at that time was worthy to be respected and that desire has successfully pioneered a new phenomenon in freeing themselves and society from the shackles of colonialism and ignorance. His contribution is very prominent in the 1900s in the field of education through developing a knowledge culture among the community thus opening the eyes of some people to come forward correcting the flaws of governance structure and introducing the ideas of Islam that meet people's lifestyles. Because of his prominence, Tok has been regarded as a leading figure in the reform of the Malay world and upholding Islam as the complement to people’s lifestyles. However, his involvement in political groups was not as prominent as other Islamic reform activists. He has his own way to change the mindset of the people in the Malay Archipelago at that time by founding the Pondok institution and he is so serious about developing this institution either in Kelantan or elsewhere.